2020
DOI: 10.3390/nu12030768
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with the 2018 World Cancer Research Fund/American Institute for Cancer Research Cancer Prevention Recommendations and Prostate Cancer

Abstract: The etiology of prostate cancer (PCa) remains largely unknown. Compliance with the 2018 World Cancer Research Fund/American Institute for Cancer Research (WCRC/AICR) cancer prevention recommendations and its relationship to PCa was evaluated. A total of 398 incident PCa cases and 302 controls were included. The selection criteria for both cases and controls were: (i) age between 40–80 years; and (ii) residence in the coverage area of the reference hospitals for 6 months or more prior to recruitment. A score to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 41 publications
1
33
1
Order By: Relevance
“…To date, there have been few studies evaluating the association between updated recommendations and the risk of other cancers. Studies on total cancer incidence in Sweden [ 56 ] and cancers of the colon in Spain [ 57 ] and the USA [ 58 ], breast in Spain [ 59 ] and the USA [ 60 ], and prostate in Spain [ 61 ], similarly to the current study, found a positive association with adherence to the 2018 WCRF/AICR recommendations. In contrast, one arm of the EPIC project focused on breast cancer in Europe [ 35 ], and a clinical-control study focused on chronic lymphocytic leukaemia in Spain [ 62 ] found no association with adherence to the 2018 WCRF/AICR recommendations.…”
Section: Discussionsupporting
confidence: 81%
“…To date, there have been few studies evaluating the association between updated recommendations and the risk of other cancers. Studies on total cancer incidence in Sweden [ 56 ] and cancers of the colon in Spain [ 57 ] and the USA [ 58 ], breast in Spain [ 59 ] and the USA [ 60 ], and prostate in Spain [ 61 ], similarly to the current study, found a positive association with adherence to the 2018 WCRF/AICR recommendations. In contrast, one arm of the EPIC project focused on breast cancer in Europe [ 35 ], and a clinical-control study focused on chronic lymphocytic leukaemia in Spain [ 62 ] found no association with adherence to the 2018 WCRF/AICR recommendations.…”
Section: Discussionsupporting
confidence: 81%
“…[6][7][8][9][10][11][12] There are also recent studies which used the 2018 WCRF/AICR Score. [13][14][15] Several studies investigated knowledge, attitudes and behaviors related to dietary habits, physical activity and cancer prevention among the younger population such as university students, but to the best of our knowledge no study used the 2018 WCRF/AICR Score, which focuses on promoting a healthy diet across the lifespan, favorable to the prevention of different types of cancer as well as other chronic diseases. [16][17][18][19][20][21] University students transit a life period when they become more independent, have a busy schedule, maybe even live apart from their parents, and hence being responsible for choosing, buying and cooking their food, deciding the content, the quantity and the time of their meals and snacks as well as other lifestyle behaviors such as physical activity and alcohol consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Participants were recruited between May 2017 and September 2020. Previous studies have extensively described the methodology of the CAPLIFE study [ 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%